The installation of deep foundation (pile) using jack in machine / Mohd Asyraf Mohd Rozaidi - Mohd Rozaidi, Mohd Asyraf (Universiti Teknologi MARA, Perak, 2018)
Pilings are wooden, metal, or concrete posts which are pushed into the ground and on which buildings or bridges are built. Pilings are often used in very wet areas and at the weak soil areas so that deep foundation is suitable at that type of site. The purpose of the piling is to improve the strength of the soil so that the soil will receive the load from the building. The method starts with a pile driving apparatus driving jack in piling system had two hydraulic cylinder barrels moving along two vertical support structures. An uppermost horizontal member is employed to maintain a working space in between the two vertical support structures. The actuating rods are fixed to the uppermost horizontal member.